The diffusion of process innovations in industrialized and developing countries: a case study of the world textile and steel industries - Matthias Lücke (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
This paper tests the hypothesis that industrial process innovations diffuse more slowly in developing countries than in industrialized countries. The focus of the analysis is on four innovations in the textile and steel industries, selected according to data availability. The analysis uses a variable coefficient regression model, based on an S-shaped diffusion curve. It is found that, overall, the level of economic development had only a modest impact on the adoption of innovations. At a more disaggregated level of analysis, its (limited) impact was related to both the characteristics of the technology, and to the firm structure of the respective industry.
Keywords: 330; Innovationsdiffusion; Textil- und Bekleidungsindustrie; Stahlindustrie; Industriestaaten; Entwicklungsländer